Flavonoids in treatment of chronic kidney disease - Cao, Yi-Ling; Lin, Jihong; Hammes, Hans-Peter; Zhang, Chun (Molecules, 2022)
Chronic kidney disease (CKD) is a progressive systemic disease, which changes the function and structure of the kidneys irreversibly over months or years. The final common pathological manifestation of chronic kidney disease is renal fibrosis and is characterized by glomerulosclerosis, tubular atrophy, and interstitial fibrosis. In recent years, numerous studies have reported the therapeutic benefits of natural products against modern diseases. Substantial attention has been focused on the biological role of polyphenols, in particular flavonoids, presenting broadly in plants and diets, referring to thousands of plant compounds with a common basic structure. Evidence-based pharmacological data have shown that flavonoids play an important role in preventing and managing CKD and renal fibrosis. These compounds can prevent renal dysfunction and improve renal function by blocking or suppressing deleterious pathways such as oxidative stress and inflammation. In this review, we summarize the function and beneficial properties of common flavonoids for the treatment of CKD and the relative risk factors of CKD.
Published: 6 April 2022
Gesehen am 13.06.2022